Effects of interaction between zinc oxide and copper sulfate on starter pig performance - J W Smith II; B T Richert; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1994)
Two experiments were conducted to examine the effects of supplementing starter pig diets with zinc oxide and (or) copper sulfate on starter pig performance. In experiment 1, two hundred forty pigs were used in a 28-day growth assay. Four dietary treatments were used: 1) control (165 ppm zinc and 16.5 ppm copper), 2) 3,000 ppm zinc, 3) 250 ppm copper, and 4) 3,000 ppm zinc + 250 ppm copper. The pigs were blocked by weight and allotted to each of the four dietary treatments in a 2 x 2 factorial design with 9, 10, or 11 pigs per pen and 6 replicate pens per treatment. Diets were formulated in two phases: Phase I (d 0 to 14 postweaning) and Phase II (d 14 to 28 postweaning) with 1.6 and 1.25% lysine, respectively. Pigs were fed the same experimental mineral level during the entire 28-d growth assay. During Phase I, feeding 3,000 ppm zinc from zinc oxide, with or without 250 ppm copper, improved average daily gain (ADG) and feed efficiency (F/G) compared with pigs fed the control or added-copper diets. Surprisingly, no improvement occurred in ADG or F/G for pigs fed the diet with 250 ppm copper from copper sulfate as compared with pigs fed the control diet. In Phase II, a zinc x copper interaction occurred. Pigs fed the diet with only added zinc grew faster, ate more, and were more efficient than pigs fed the control diet. Pigs fed diets with added copper had intermediate ADG and average daily feed intake (ADFI). Pigs fed diets with added zinc and (or) copper had similar F/G. For the entire 28-day trial, pigs fed the diets with added zinc had improved ADG, ADFI, and F/G compared to pigs fed the control diet. In the second experiment, pigs were fed a common Phase I diet supplemented with zinc oxide (3000 ppm zinc). On d 14, pigs were switched to the diets containing experimental mineral levels. Phase II experimental diets were identical to those of the first experiment. Similar to Phase II in Exp. 1, a zinc x copper interaction occurred for ADG. Zinc oxide improved ADG when added to the control diet, but not when added to the copper diet. Feeding high levels of zinc oxide in the Phase I diets may have had a carryover effect in Phase II, because we found no improvement in pig performance when high levels of copper were added to the Phase II diet. The results from these experiments indicate that feeding 3,000 ppm of zinc from zinc oxide is a viable means of increasing starter pig performance, but optimum response occurs when the diet does not contain supplemental copper from copper sulfate.; Swine Day, Manhattan, KS, November 17, 1994
Keywords: Swine day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-175-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 717; Swine; Starter; Performance; Zinc oxide; Copper sulfate